The Maverick and his machine : - Maney, Kevin (John Wiley & Sons, Inc., 2003)
The story of Watson's transformation of the disorganized, amorphous Computing-Tabulating-Recording Company into streamlined, world-famous IBM receives a spirited telling by Maney, a USA Today technology columnist. Access to previously unexplored records has provided juicy raw material, including letters and internal memos, to bring America's first celebrity CEO to life in this warts-and-all biography. Watson (1874- 1956) saw the strategic value of corporate culture early and was protective of what he built; Maney argues that the strength of that culture later allowed IBM to survive the potentially devastating effects of Watson's personality flaws.